Keberkesanan Proses Pengurusan Pengetahuan Sektor Awam Melalui Sokongan Teknologi Maklumat dan Komunikasi (ICT) - Mohammad Hadil, Berahem (2010)
This study was conducted at the Hospital Melaka and Jabatan Kesihatan Negeri Melaka and agencies under it to represent the public sector in Malaysia. The study was implemented to evaluate the extent of knowledge management process that is practiced in the public sector and also the best method or approach that can be used to promote knowledge management as a best practice in realizing the organizational knowledge . This study examines the use of ICT support that involves the relationship between the three (3) critical success factors that are technology infrastructures, ICT systems and applications of users and users ICT training with the knowledge management process. A total of 350 questionnaires were distributed to the location of the study and 256 or 73.14% of the respondents was collected, comprising civil servants scheme management, clinical and clinical support. The data was analyzed using statistical research software that is the Statistical Package Social Science (SPSS) version 18.0. The findings showed that the effectiveness of knowledge management can help organizations carry out their daily duties in the public sector is at the level of 81.3% (n = 208). In view of the elements to ICT support in public sector organizations to develop and acquire knowledge effectively, the majority are agreed with the rate 93.8% (n = 240). To examine the relationship between support for the use of ICT and knowledge management processes Pearson correlation was used and showed the three critical success factors supporting the use of ICT has a significant relationship with knowledge management processes at the level of significance p = 0.05. To find the effect of the use of ICT support to knowledge management processes, multiple regression analysis conducted and found that only the technology infrastructure that can only affect the effectiveness of knowledge management processes of public sector organizations.